CT-on-rails-guided HDR brachytherapy: single-room, rapid-workflow treatment delivery with integrated image guidance. (March 2014) - Orcutt, Kevin P; Libby, Bruce; Handsfield, Lydia L; Moyer, Grace; Showalter, Timothy N
ABSTRACT: : Brachytherapy is an important component of multidisciplinary cancer care for a variety of solid tumors. Most systems require moving the patient to multiple locations for treatment planning and delivery after the applicator is placed. A dedicated computed tomography (CT)-on-rails brachytherapy suite was installed at our institution to allow image-guided brachytherapy and a rapid scan–plan–treat workflow that is well suited to a busy quaternary care medical center. The suite consists of an OR couch with CT-compatible insert, a CT-on-rails imaging unit, a Varian Varisource iX HDR afterloader and full anesthesia capabilities. The explicit goal was to provide the ability to perform applicator placement, CT-guided treatment planning, and treatment delivery efficiently and without moving the patient. The dedicated CT-on-rails suite for high-dose-rate brachytherapy offers image-guided brachytherapy capabilities with a rapid workflow that lends itself well to efficient, high-quality care that can meet the demands of a large-volume referral center capable of high patient throughput.